High sensitivity troponin might be a marker of subclinical scleroderma heart involvement: a preliminary study. Issue 3 (September 2017) - Barsotti, Simone; Stagnaro, Chiara; d'Ascanio, Anna; Parma, Alice; Emdin, Michele; Conti, Umberto; Mosca, Marta; Della Rossa, Alessandra
Introduction: Although often asymptomatic, cardiac involvement is common in systemic sclerosis (SSc), and is associated with an increased morbidity and mortality. The aim of this study is to investigate whether high-sensitivity troponin (HSTn) might represent a useful tool to detect subclinical scleroderma heart involvement (SHI) in SSc. Methods: We enrolled 65 consecutive SSc patients who performed HSTn test, electrocardiogram and an echocardiogram within six months of HSTn test. We acquired also data about N-terminal segment of proBNP (NT-proBNP) and cardiac magnetic resonance imaging (cMRI). We excluded patients with overt pulmonary arterial hypertension. We defined as subclinical SHI the presence of the following conditions: diastolic dysfunction, pericardial effusion, conduction abnormalities/arrhythmias, oedema and/or T2 weighted non-ischemic pattern showed by cMRI. Results: Twelve patients showed SHI, and 23 and 29, respectively, had high levels of HSTn and of NT-proBNP. SHI is correlated with high levels of HSTn (p = 0.02) with a significant difference between HSTn values in patients with or without SHI (59 vs. 13 ng/mL; p = 0.0097). Moreover, among patients with abnormal NT-proBNP, 18 also had out of range HSTn (Spearman rank correlation 0.5; p<0.0001). According to ROC curve analysis, the best HSTn cut-off value in distinguishing between patients with and patients without SHI was 16 ng/mL (sensitivity 66.7%, specificity 83%; area under the curve: 0.77 (95% CI: 0.65-0.87) p<0.001. Conclusions: Our data show a close relationship between HSTn and NT-proBNP in SSc patients with SHI. HSTn might be a marker of SHI while NT-proBNP seems to be less specific for heart dysfunction.